الحملات الأوربية على الجزائر في العهد العثماني رد فعل على الأسر ونشاط القرصنة - بوعلام صفاح (University of Eloued جامعة الوادي, 2024)
Thanks to the strength of its military apparatus and the effectiveness of its naval fleet, thanks to which it was able to impose its sovereignty on the international arena, the European countries were forced to submit to its will, but with the geopolitical changes that occurred in the western basin of the Mediterranean and the imbalance of power, where collective European attitudes rejecting the activity of The Algerian Navy and related to piracy and captivity and considered harassment and illegal activity. The manifestations of refusal were represented in several European countries launching naval military campaigns against Algeria, with the aim of liberating its prisoners and recovering its ships seized by Algerian sailors. استطاعت إيالة الجزائر بفضل قوة جهازها العسكري وفعالية أسطولها البحري، والذي تمكنت بفضلها من فرض سيادتها على الساحة الدولية، أجبرت الدول الأوربية على الخضوع لإرادتها، لكن مع التغيرات الجيوسياسية التي وقعت في الحوض الغربي للمتوسط واختلال موازين القوى، حيث بدأت تظهر مواقف جماعية أوربية رافضة لنشاط البحري الجزائري والمتعلقة بالقرصنة والأسر واعتباره تحرش ونشاط غير قانوني. وقد تمثلت مظاهر الرفض في قيام عديد الدول الأوروبية بحملات عسكرية بحرية ضد الجزائر، بغية تحرير أسراها واسترداد سفنها المحجوزة لدى البحارة الجزائريين.
Keywords: الأسرى المسيحيين; الجزائر; العهد العثماني; الحملات الأوربية البحرية; Christian captives; Algeria; Ottoman era; European Naval Campaigns